Toponymic information system for description and classification of ethno-informatics of "kampung" naming in the East Priangan of West Java. Issue 1 (January 2021) - Sudrajat, R; Setiana, D; Rejito, J; Pradana, A; Suryana, I; Suryani, M; Zakaria, M M; Permana, F C; Ruchjana, B N; Abdullah, A S
Abstract: The toponymy of naming places in social culture in certain places can describe the characteristics of the society in the past, therefore it is interesting to study how the ancestors of the society culture named their place. This research describes and classifies the naming based on the word structure, including prefixes, syllables it contains, and the complete word in the naming of a "kampung" which is covered in village, describing and classifying the meaning of the naming of the "kampung" based on particular categories, mapping the naming of the "kampung" on the map of the location, as well as developing the study location of the composition of the intersection of sets by taking the sample of "kampung" naming database in districts in East Priangan areas of West Java. The system development method used in this research is the waterfall software development method. Waterfall is a systematic classical model employed in developing software. The stages of Waterfall consists of Communication (Project Initiation & Requirements Gathering), Planning (Estimating, Scheduling, tracking), Modelling (Analysis Design), Construction (Coding and System Test), Deployment (Delivery, support, feedback), and Maintenance. The result of the study showed that 8, 75% of the "kampung" names mostly start with the prefix "Ci", "Pa", "Su" with 8, 75%, 9, 62%, and 5, 12% respectively. The syllable mostly contains the meaning of nature, place, feeling, and communication. The meaning of "kampung" naming represents the character of the society, which becomes the guidance for them in living their daily life: loving the nature and the environment, religious spirit, artistic soul, being hard worker, respecting the ancestors, soft feeling, and loving communicating. The result of the intersection of sets of the "kampung" names can help the researchers to determine the destination of the study location under the study, while the set composition describes the taking of each set composition which has the different number of the intersection of set members. The visualization of village naming makes the reading of "kampung" naming at each location of the research easy, both for the similarity and the typical nature of each area under the study.